2016
DOI: 10.1038/srep38193
|View full text |Cite
|
Sign up to set email alerts
|

Bonobo personality traits are heritable and associated with vasopressin receptor gene 1a variation

Abstract: Despite being closely related, bonobos and chimpanzees show remarkable behavioral differences, the proximate origins of which remain unknown. This study examined the link between behavioral variation and variation in the vasopressin 1a receptor gene (Avpr1a) in bonobos. Chimpanzees are polymorphic for a ~360 bp deletion (DupB), which includes a microsatellite (RS3) in the 5′ promoter region of Avpr1a. In chimpanzees, the DupB deletion has been linked to lower sociability, lower social sensitivity, and higher a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 57 publications
3
40
0
Order By: Relevance
“…Results consistent with these findings have been found in studies that use behavioural measures, including one of semi-free-ranging female rhesus macaques [67] and one of zoo-housed bonobos [75].…”
Section: (C) Heritabilitysupporting
confidence: 79%
See 1 more Smart Citation
“…Results consistent with these findings have been found in studies that use behavioural measures, including one of semi-free-ranging female rhesus macaques [67] and one of zoo-housed bonobos [75].…”
Section: (C) Heritabilitysupporting
confidence: 79%
“…Studies using these statistical methods have found a moderate proportion of the variation in rating-based personality dimensions of chimpanzees [72,73], orangutans [74] and bonobos [75] to be attributable to additive genetic effects. Results consistent with these findings have been found in studies that use behavioural measures, including one of semi-free-ranging female rhesus macaques [67] and one of zoo-housed bonobos [75].…”
Section: (C) Heritabilitymentioning
confidence: 99%
“…Staes et al (2015) also looked at captive chimpanzee personality, but used observed rates of specific behaviors to assess personality rather than questionnaire ratings, and reported that the long allele was associated with total time spent giving and receiving grooming. Staes et al (2016) reported a study of the same polymorphism in captive bonobos rather than chimpanzees, using both observer questionnaires and behavioral rate observations, and found the long allele associated with higher “attentiveness” and lower “openness.” To our knowledge only Staes et al (2015) has examined OXTR in NHPs social behavior, which reported no effect of an intronic SNV.…”
Section: | Introductionmentioning
confidence: 99%
“…Research on zoohoused Chimpanzees (Weiss et al, 2000;Wilson, V. A. D., et al, 2017), orangutans Pongo spp (Adams et al, 2012) and Bonobos Pan paniscus (Staes et al, 2016) has indicated that personality variation appears to be partly related to genetic differences between individuals and partly related to the influences of environmental effects that operate at the within-zoo or within-family level. At the time of writing, no comparable study has been conducted on gorillas Gorilla spp.…”
Section: Genetics Of Personalitymentioning
confidence: 99%
“…Reif & Lesch, 2003). Studies of Chimpanzees living at Yerkes National Primate Research Center (Atlanta, GA, USA) (Hopkins et al, 2012;Latzman et al, 2015), and those living mostly in zoos, research centres and a sanctuary in Japan, amounting to 129 Chimpanzees including 19 that lived at a sanctuary in Guinea (Wilson, V. A. D., et al, 2017), found evidence that versions of a gene for receptors for the hormone vasopressin are associated with the personality dimension Conscientiousness, which describes how tame and predictable individuals are [see Staes et al (2016) for a similar finding in Bonobos]. However, the effects of single genes are very small, typically accounting for <1% of trait variation.…”
Section: Genetics Of Personalitymentioning
confidence: 99%